A study on reforming personnel cultivation pattern of Chinese physical education Institutes and Universities after the 2008 Olympic Games - Wang, K.; Li, Y.; Huang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In order to meet the demand of providing talented athletes for the 2008 Beijing Olympic Games, a large number of multi-skill talented people have been trained by professionals at government agencies and universities who have both knowledge and skills in specific disciplines. However, the development of careers in the field of sports and physical education present some new challenges to the sports administration system as a function of the rapid development of professional sport events, community sports, school physical education, fitness and wellness clubs, and construction of sports industry unions. These new changes place higher demands on the Chinese physical education system. How to reform the system to meet these challenges has become a subject of Chinese physical education institutes and universities that needs to be resolved urgently. Methods Review of literature and documentation of expert interviews, questionnaires and surveys and statistical analysis of data and logical analysis. Results The main problems of talent cultivation at Chinese physical education institutes and universities can be summarized as follows: 1) The aim of cultivating talent was not clear and the development of talents standards needs to be updated. 2) The training system does not meet community demands nor fits the condition of the institution and the student sources, 3) The curriculum system is incomplete and specialty characteristics are unclear. Specialty education has been given more attention than basic education and quality education. 4) The form of teaching and practical training is single dimensional and lacks practical application to integrate teaching with learning. The accreditation system has not been functioning effectively. Discussion Based on the results of surveys on society demand, school conditions, and the student sources, it is important to set appropriate goals for cultivating talents and to optimize the development of specialty structures and systems following the principle of social adaptation, market demand, and quality assurance. In addition, practical training systems should be established for inside and outside class teaching and learning activities. An accreditation system should be set up to monitor and control the operating system and its mechanism. Educational agencies or other organizations should establish a system to evaluate and monitor the quality of the control system more effectively. The senior talent incentive policy should be in place to cultivate a characteristic rank for teachers with high educational levels and strong practicing ability. Finally, research studies should be conducted to advance the knowledge and evaluation of the systems proposed.